2009
DOI: 10.4103/0250-474x.51941
|View full text |Cite
|
Sign up to set email alerts
|

Drug use in pregnancy; a point to ponder!

Abstract: Pregnancy is a special physiological condition where drug treatment presents a special concern because the physiology of pregnancy affects the pharmacokinetics of medications used and certain medications can reach the fetus and cause harm. Total avoidance of pharmacological treatment in pregnancy is not possible and may be dangerous because some women enter pregnancy with medical conditions that require ongoing and episodic treatment (e.g. asthma, epilepsy, hypertension). Also during pregnancy new medical prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
143
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(164 citation statements)
references
References 13 publications
(20 reference statements)
0
143
0
7
Order By: Relevance
“…4,5 Pharmacological treatment should be avoided in pregnancy, unless absolutely necessary. [6][7][8] Pregnant women are generally excluded, for ethical reasons, from randomized clinical trials in drug development. This has left questions about the safety of new medications on the developing fetus unanswered, upon drug approval and marketing.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Pharmacological treatment should be avoided in pregnancy, unless absolutely necessary. [6][7][8] Pregnant women are generally excluded, for ethical reasons, from randomized clinical trials in drug development. This has left questions about the safety of new medications on the developing fetus unanswered, upon drug approval and marketing.…”
Section: Introductionmentioning
confidence: 99%
“…The Food and Drug Administration (FDA) has established five distinguishing categories to designate the potential for a drug to cause birth defects if used during pregnancy [66] and reflect both documentation reliability and relative risk to benefit ratio considerations (Table 1).…”
Section: Managementmentioning
confidence: 99%
“…7,8 Teratogenic drugs are responsible for <1% of birth defects. 9 Previous studies had reported only 24% of physicians to be confident while prescribing for a pregnant woman. 10 During pregnancy 59% of women are prescribed with drugs other than vitamin and mineral supplements.…”
Section: Introductionmentioning
confidence: 99%
“…10 During pregnancy 59% of women are prescribed with drugs other than vitamin and mineral supplements. 9 Category D drugs were used in 0.41% to 23% and category X drugs were used in 0 to 2.9% of the cases during pregnancy. 7,11 There is a need for the early exposure of students to the concept of teratogenicity which will bridge the gap in their knowledge as well as which will lay the foundation for safe prescribing for a pregnant woman.…”
Section: Introductionmentioning
confidence: 99%